Development of a technology for eliminating color rendering imperfections in digital photographic images - Kovalskyi, Bohdan; Dubnevych, Myroslava; Holubnyk, Tetyana; Pysanchyn, Nadiia; Havrysh, Bohdana (Eastern-European Journal of Enterprise Technologies, 2019)
Complexity of integrating color control systems into a workflow for obtaining digital half-tone images results in appearance of color rendering imperfections in photographic images as exposure conditions constantly vary in power and spectral composition of radiation. A wide range of corrective means in graphic editors does not ensure full elimination of color rendering imperfections in photographic images because of imperfect technical approaches to realization of the corrective effect. The process of correcting color rendering imperfections is complicated by the lack of methods for objective quantitative assessment of qualitative characteristics of digital color halftone images. The developed method of quantitative assessment of color characteristics of digital images by conversion of actinicity in values of effective densities provides optimal and comprehensive analysis of color rendering accuracy. The procedure consists in representation of color separation characteristics in a form of dependence of effective densities of the photographic image on grey-equivalent densities of the recorded object. It becomes possible to numerically evaluate imperfections of color rendering in a digital color photographic image. The developed assessment procedure has become the basis for implementation of a new method for correcting color rendering imperfections with the help of compensatory corrective images ensuring elimination of the imperfection of insufficient color. The correction effect is provided by the physical content of compensatory images which contain effective densities for the separated colors which are absent in digital photographic images because of non-isoactinism of isochrome colors. The new technology for correcting color rendering is implemented in the developed Image Redactor specialized software. Effectiveness of the described method was proved on the basis of analysis of images processed in the created software product according to the method of graphical representation of color separation characteristics described in the paper. Color separation matrices indicate a significant increase in useful contrasts of separated colors in comparison with similar characteristics of color rendering in images before their processing. This provides for the possibility of applying the developed method of correcting color rendering imperfections in the digital work flow of processing photographic images.